Number of casual male sexual partners and associated factors among men who have sex with men: Results from the National HIV Behavioral Surveillance system - Salazar Laura F; DiNenno Elizabeth A; Sullivan Patrick S; Rosenberg Eli S; Sanchez Travis H (BMC, 2011)
Abstract Background In 2006, the majority of new HIV infections were in MSM. We sought to describe numbers of casual sex partners among US MSM. Methods Data are from the first MSM cycle of the National HIV Behavioral Surveillance system, conducted from 2003 to 2005. Relationships between number of casual male sex partners within the previous year and demographic information, self-reported HIV status, and risk behaviors were determined through regression models. Results Among 11,191 sexually active MSM, 76% reported a casual male partner. The median casual partner number was three. Lower number of casual partners was associated with black race, Hispanic ethnicity, and having a main sex partner in the previous year. Factors associated with a higher number included gay identity, exchange sex, both injection and non-injection drug use. Being HIV-positive was associated with more partners among non-blacks only. Age differences in partner number were seen only among chat room users. Conclusions MSM who were black, Hispanic or had a main sex partner reported fewer casual sex partners. Our results suggest specific populations of MSM who may benefit most from interventions to reduce casual partner numbers.